Predictors of major procedure-related complications in transvenous lead extraction. (25th November 2020) - Doring, M; Ebert, M; Lucas, J; Hindricks, G; Richter, S
Abstract: Background: Transvenous lead extraction (TLE) has become the mainstay therapy for device-related infections. Though TLE procedures are associated with low complication and high success rates, risk factors for major procedure-related complications remain not well defined. Purpose: To evaluate the safety and efficacy of TLE in a large single centre cohort and to identify risk factors for major complications. Methods: All consecutive patients who had undergone TLE in our department between May 2012 and January 2020 were included in a prospective registry. Our protocol for TLE followed a stepwise approach according to lead dwell time and estimated complexity of the procedure: use of simple traction ± locking stylet (LS) ± mechanical and/or powered sheaths ± snare technique. In case of unsuccessful extraction from the venous entry site, femoral or jugular access was approached. Patient characteristics, procedural data and complications were gathered and analysed. Logistic regression analysis was applied to identify risk factors for major procedure-related complications. Results: A total of 1717 leads (443 [25.9%] ICD leads) were targeted for TLE in 810 patients (67±15 years; 76% male). The mean lead dwell time was 83±60 months. The leading indication for TLE was cardiac device related infection (CDRI) in 527 patients (65.1%), of whom 273 (51.8%) had systemic and 254 (48.2%) localized infection. Two hundred eighty-three patients (34.9%) underwent TLE for non-CDRI causes. Leads were extracted by simple traction in 28.2%, traction with LS in 4.1%, dilator sheaths with LS in 50.1%, and additional use of powered mechanical sheaths in 13.0%. The snare technique was used in 4.6%. Venous access for TLE was exclusively from the entry site in 94.8%, combined from femoral in 4.0% and jugular in 1.2%. TLE was completely successful in 96.2%, partially successful in 2.1%, and failed in 1.7% of all attempted leads, which translated to a clinical success rate of 96.8%. Eighteen patients (2.2%) experienced minor and 12 patients (1.5%) had major procedure-related complications (cardiac tamponade/perforation) including one intraprocedural death (0.1%) from fulminant pulmonary embolism. Lead-years-per-patient (HR 1.064, 95% CI 1.032–1.096; p<0.001), dwelling time of the oldest lead (HR 1.013, 95% CI 1.007–1.019; p<0.001), and BMI (HR 0.877, 95% CI 0.772–0.997; p=0.020) were significant predictors for major complications in logistic regression analysis. Conclusion: TLE is feasible, effective and safe in our large single centre experience. Overall complication and failure rates are low. Following our TLE protocol, dwelling time of the extracted leads and low BMI were associated with major procedure-related complications. Funding Acknowledgement: Type of funding source: None